Soft corals (Cnidaria, Alcyonacea) from the Gulf of Nicoya estuary, Pacific of Costa Rica: a checklist (UNED Research Journal, 2021)
Introduction: The Gulf of Nicoya is the most important estuary on the Pacific coast of Costa Rica. Information on the presence of soft corals is scattered in the literature and in museum collections. Objective: To provide a list of soft corals reported for the estuary. Methods: We compiled the literature (2002-2020) and of the specimens deposited at the Museum of Zoology, University of Costa Rica. Results: Thirty species have been reported for the estuary (Clavulariidae, Gorgoniidae and Plexauridae). Most were collected on the eastern coast of the Nicoya Peninsula, and several species were described based on estuary specimens. Conclusion: The 30 species represent 79 % of those reported for Costa Rica. Despite this relatively high percentage, the sampling effort has been modest and other sites within the estuary should be explored.
Keywords: Adelogorgia; Carijoa; Leptogorgia; Muricea; Pacifigorgia; Eastern Tropical Pacific; Octocorallia